1997
DOI: 10.1164/ajrccm.155.1.9001305
|View full text |Cite
|
Sign up to set email alerts
|

Lower respiratory illness, recurrent wheezing, and day care attendance.

Abstract: We prospectively assessed the relations between various characteristics of day care and lower respiratory illness (LRI) in a cohort of 1,268 Minnesotan children, born between October 1989 and January 1991 and followed to 2 yr of age. Information on LRI was abstracted from medical records and data on day care use, respiratory symptoms, and physician diagnosis of asthma were obtained from questionnaires. We identified a subgroup of 60 children with recurrent wheezing illnesses. The LRI rate ratio for day care at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
1
18

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 16 publications
4
74
1
18
Order By: Relevance
“…Anderson et al 2 did not find any association between LRI and child-care homes, while Marbury et al 24 and Holberg et al 18 found no difference between the various forms of child care studied. In fact, in both studies, groups of 3 or more children were already at a higher risk than home cared children independently of child-care setting.…”
Section: Lower Respiratory Infections (Lri)mentioning
confidence: 92%
See 2 more Smart Citations
“…Anderson et al 2 did not find any association between LRI and child-care homes, while Marbury et al 24 and Holberg et al 18 found no difference between the various forms of child care studied. In fact, in both studies, groups of 3 or more children were already at a higher risk than home cared children independently of child-care setting.…”
Section: Lower Respiratory Infections (Lri)mentioning
confidence: 92%
“…Adjusted analyses were not reported. Marbury et al 24 found an overall relative risk of 2 for children in child care. The adjusted relative risks found for care at own home (with someone other than the parents), child-care homes and child-care centers were 1.7 (1.4-2.1), 2.0 (1.7-2.3) and 2.3 (1.9-2.8).…”
Section: Lower Respiratory Infections (Lri)mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8] The risks of these infectious diseases are affected by several factors including birth weight, gestational age, socioeconomic status, ethnicity, number of siblings, day care attendance, and parental smoking. 3,5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20] Breastfeeding has been suggested as a modifiable influencing factor. When given exclusively, breastfeeding reduces the risk of infectious diseases in infants in developing countries.…”
mentioning
confidence: 99%
“…Os trabalhos científicos existentes são praticamente unânimes em mostrar que as crianças que freqüentam creches adoecem mais freqüente-mente que as crianças cuidadas exclusivamente em casa (Haskins & Kotch, 1986;Barros, 1999). Em particular, crianças que freqüentam creches apresentam uma ocorrência de pneumonia 2 a 12 vezes maior que as crianças cuidadas em casa (Victora et al, 1994;Fonseca et al, 1996;Marbury et al, 1997). Diarréia é outro problema que ocorre com freqüência 60 a 250% maior nas crianças em creches (Alexander et al, 1990;Hillis et al, 1992).…”
Section: Introductionunclassified